2015
DOI: 10.1002/imhj.21530
|View full text |Cite
|
Sign up to set email alerts
|

Attention Functioning in Children With Prenatal Drug Exposure

Abstract: Children born to drug abusers are exposed to teratogenic influences on intrauterine brain development and undergo postnatal withdrawal. We investigated the interplay of different domains and levels of attention functioning in 24 prenatally exposed and 25 nonexposed children who were 5 to 6 years old. Assessment included parent ratings and neuropsychological and electrophysiological methods. Exposed children had a higher prevalence of attention deficit hyperactivity symptoms, tended to have poorer performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
4
0
3
Order By: Relevance
“…These medications included Clonidine, Adderall, Concerta, Tenex, Straterra, and combinations thereof. Prior research has shown that IUDE children exhibit extreme difficulties with self-regulation across numerous domains associated with attention including arousal, emotional reactivity, sustained attention (Accornero et al, 2007;Gabriel & Taylor, 1998;Garavan et al, 2000;Gendle et al, 2003;Jaeger et al, 2015;Noland et al, 2005;Slinning, 2004;Willford et al, 2018), and in some cases at our clinic a lack of understanding about the importance and significance of giving an appropriate effort on these types of tests. Close monitoring during test administration in these children and clear instructions are good clinical practice to increase the accuracy of the results.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These medications included Clonidine, Adderall, Concerta, Tenex, Straterra, and combinations thereof. Prior research has shown that IUDE children exhibit extreme difficulties with self-regulation across numerous domains associated with attention including arousal, emotional reactivity, sustained attention (Accornero et al, 2007;Gabriel & Taylor, 1998;Garavan et al, 2000;Gendle et al, 2003;Jaeger et al, 2015;Noland et al, 2005;Slinning, 2004;Willford et al, 2018), and in some cases at our clinic a lack of understanding about the importance and significance of giving an appropriate effort on these types of tests. Close monitoring during test administration in these children and clear instructions are good clinical practice to increase the accuracy of the results.…”
Section: Discussionmentioning
confidence: 93%
“…IUDE children also show characteristics of attention-deficit/hyperactivity disorder (ADHD), tend to have poorer performance in an attention test battery and show EEG alterations in P300 and N200 event-related potential (ERP) measures. These findings suggest that there may be deleterious long-term effects of prenatal drug exposure on executive function domains of attention, classification, and decision-making (Jaeger, Suchan, Schölmerich, Schneider, & Gawehn, 2015). Studies of prenatal development have shown important interdependencies between the insula and amygdala in affective and social adaptivity (Bellucci, Feng, Camilleri, Eickhoff, & Krueger, 2018;Di Cesare, Marchi, Errante, Fasano, & Rizzolatti, 2018;Grecucci, Giorgetta, Bonini, & Sanfey, 2013;Klumpp, Post, Angstadt, Fitzgerald, & Phan, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…The effects of IUDE can persist over the developmental continuum into adulthood, and the deficits seen across populations can vary (Bard, Coles, Platzman, & Lynch, 2000;Bhide & Kosofsky, 2009;BuckinghamHowes, Mazza, Wang, Granger, & Black, 2016;Derauf, Kekatpure, Neyzi, Lester, & Kosofsky, 2009;Jaeger, Suchan, Schölmerich, Schneider, & Gawehn, 2015;Nadebaum, Anderson, Vajda, Reutens, & Wood, 2012;Pulsifer, Radonovich, Belcher, & Butz, 2004;Robey, Buckingham-Howes, Salmeron, Black, & Riggins, 2014); however, executive functions, social and emotional delays, and integration of social cues and rules appear to be the most prevalent issues seen in the clinical experience of the current authors.…”
Section: Introductionmentioning
confidence: 78%
“…Aktuelle Studien zeigen, dass bei Testung im Schulkindesalter nach intrauteriner Drogenexposition Störungen in den Teilleistungsbereichen wie Konzentrationsvermögen sowie räumlichem Denken nachgewiesen wurden. Diese waren allerdings nur z. T. statistisch signifikant, teilweise zeigte sich nur eine starke Tendenz diesbezüglich [14,15]. Eine Studie aus Deutschland belegt zudem eine vermehrte Häufigkeit externalisierender Verhaltensstörungen bei separater Analyse für Opioide [15].…”
Section: Resultate Zu Langzeitkonsequenzen Der Intrauterinen Drogenexunclassified
“…Diese waren allerdings nur z. T. statistisch signifikant, teilweise zeigte sich nur eine starke Tendenz diesbezüglich [14,15]. Eine Studie aus Deutschland belegt zudem eine vermehrte Häufigkeit externalisierender Verhaltensstörungen bei separater Analyse für Opioide [15].…”
Section: Resultate Zu Langzeitkonsequenzen Der Intrauterinen Drogenexunclassified